Diversity of Aquatic Insects and Function of Fluvial Ecosystem of Song River of Rajaji National Park, India (Global Journal of Science Frontier Research, 2014)
Aquatic insect diversity of Rajaji National Park, India has been monitored for a period of twelve months. Some of the important hydrological attributes were also measured in continuity of one-month interval. Aquatic insects were sampled from two sites (S1 and S2) of the Song River of the Rajaji National Park. A significant difference in the density (t=2.86455, p
Keywords: aquatic insects; monitoring; rajaji national park; physico-chemical parameters; song river; uttrakhand